CaS: Sb3+, Na and ZnS:Sn2+: phosphor materials for the improvement of WLEDs - Phuc Dang Huu; Ton That Phung (Institute of Advanced Engineering and Science, 2022)
The remote phosphor configuration, though not the best choice for WLED color quality, is superior to the luminous flux of LEDs compared to the conformal or in-cup structures. Realizing the capability of the remote phosphor design, several studies have been done to overcome the drawback of this structure, which is the color quality. A two-film distant phosphor configuration with improved color rendering index (CRI) and color quality ratio (CQS) for WLEDs is offered in this study paper. The hue temperature of the WLEDs packets employed in this research is 8500 K. This phosphor structure is constructed by layering of a green CaS:Sb3+,Na or red ZnS:Sn2+ phosphor above the yellow YAG:Ce3+ phosphor. The additional phosphor ZnS:Sn2+ concentration will then be modified to get the best color quality. The results demonstrated an increase in CRI and CQS along with the presence of ZnS:Sn2+, indicating that the existence of ZnS:Sn2+ influences significantly on these two aspects. As a result of the increased concentration of red illumination elements inside packets, the higher the concentration of ZnS:Sn2+, the higher the CRI and CQS. The green phosphor CaS:Sb3+,Na, in the meantime, improves the luminous flux.